Composição e estrutura da comunidade fitoplanctônica a montante e a jusante das Cataratas do Iguaçu, Parque Nacional do Iguaçu, Paraná, Brasil - Menezes, Viviane Costa de (2012)
This work aimed to analyze the composition variation and structure of phytoplankton community upstream and downstream of the Iguaçu Falls, Iguaçu River, investigating the influence of these waterfalls and environmental variables on this community. Samples of phytoplankton material were carried out in two sampling stations in Iguaçu River (25° 35' S; 54° 23' W e 25° 38' S; 54° 27' W), from May 2010 to May 2011 (except November). A total of 408 taxa were identified, and Bacillariophyceae was the best represented group. There was a large difference in phytoplankton composition between the sampled stations. The total richness and density of phytoplankton groups were very low in both collection sites, and it was represented by the classes Bacillariophyceae, Chlorophyceae and Cyanobacteria. The Shannon diversity was classified as very low. The equitability, in general, was high. The Multivariate Analysis of Variance showed no significant spatial or seasonal difference for total density, total richness, equitability and Shannon diversity. However, when measured densities and richness classes (Bacillariophyceae, Chlorophyceae, Cyanobacteria) separately, significant seasonal differences were observed. The heterogeneity of the characteristics of the Iguaçu River between the sampling sites did not cause a longitudinal compartmentalization of the river regarding to the attributes of the phytoplankton community, while the seasonal variation of weather conditions influenced in a significant way the composition and structure of this community in the studied environment.